The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1021/acs.orglett.5b00528
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Gold-Catalyzed Dehydrative Cyclization/Diels–Alder Reactions: Facile Access to Indolocarbazole Alkaloids

Abstract: A gold-catalyzed synthesis of cyclic 2-oxodienes from readily prepared propargyl alcohols and the subsequent Diels-Alder reaction are reported. The dehydrative cyclization reactions proceeded smoothly, and the dienes formed in situ were demonstrated to undergo cycloaddition with a variety of dienophiles. This method offers a new strategy for the synthesis of indolocarbazole alkaloids, whereby the convergent synthetic design allows for differentiation between the indole nitrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…The application of the Mo‐catalyzed reductive cyclization to the synthesis of complex molecules is exemplified in the preparation of the Boc‐protected Arcyriaflavin A, an indolocarbazole alkaloid. The synthetic sequence is reported in Scheme …”
Section: Use Of Molybdenum Catalysts With Phosphines or Glycols As Rementioning
confidence: 99%
See 1 more Smart Citation
“…The application of the Mo‐catalyzed reductive cyclization to the synthesis of complex molecules is exemplified in the preparation of the Boc‐protected Arcyriaflavin A, an indolocarbazole alkaloid. The synthetic sequence is reported in Scheme …”
Section: Use Of Molybdenum Catalysts With Phosphines or Glycols As Rementioning
confidence: 99%
“…The synthetic sequence is reported in Scheme 70. [196] The last step in the synthesis is the reductive cyclization of a nitro substituted intermediate. The authors reported that the cyclization to get the five-membered heterocycle could not be accomplished using the uncatalyzed Cadogan reaction, Grignard reagents or different amination methods.…”
Section: Synthesis Of Five-membered Ring Heterocycles Using Phosphinementioning
confidence: 99%
“…Aponick and co‐workers made continuous efforts in gold‐catalyzed dehydrative cyclization of propargylic alcohols. In 2015, they reported a gold‐catalyzed synthesis of cyclic 2‐oxodienes from propargyl alcohols and the subsequent Diels−Alder reaction (Scheme ) . The dehydrative cyclization of the propargylic alcohol 65 generated diene 66 in situ in the presence of a gold catalyst, which then underwent cycloaddition with a variety of dienophiles.…”
Section: Gold‐catalyzed Transformation Of Propargyl Alcoholsmentioning
confidence: 99%
“…By taking advantage of the presence of the diene, Diels–Alder cycloadditions were performed , . α‐Dienyl piperidine 2a was heated with diethyl but‐2‐ynedioate to give the corresponding Diels–Alder adduct 25 in a yield of 60 % .…”
Section: Resultsmentioning
confidence: 99%